Fibroblast growth factor 23 levels decline following sleeve gastrectomy. (15th April 2019) - Billington, Emma O.; Murphy, Rinki; Gamble, Greg D.; Callon, Karen; Davies, Naomi; Plank, Lindsay D.; Booth, Michael; Reid, Ian R.
Abstract: Objective: Levels of fibroblast growth factor 23 (FGF23) have been positively associated with measures of adiposity, cardiovascular disease and mortality. It is unclear whether the relationship of FGF23 with cardiovascular disease and mortality is confounded by obesity. We aimed to determine whether FGF23 concentrations decline following a reduction in adiposity after sleeve gastrectomy (SG). Design: The effect of SG on FGF23 was evaluated in 22 obese adults (59% male) with type 2 diabetes. Fat mass, weight, BMI, plasma intact FGF23, parathyroid hormone (PTH) and leptin were determined at baseline and at 12 months following SG. Results: At baseline, median (IQR) age was 51 (43‐54) years, fat mass 47.8 (41.0‐59.4) kg, BMI 40.9 (36.9‐46.9) kg/m 2 and FGF23 66.2 (55.3‐82.9) pg/mL. Significant changes in median BMI (−10.8 kg/m 2, 95% CI: −12.9 to −7.2, P < 0.0001), fat mass (−20.0 kg, 95% CI: −26.7 to −12.4, P < 0.0001) and weight (−34.7 kg, 95% CI −40.0 to −23.1, P < 0.0001) were observed after SG. FGF23 (−12.4 pg/mL, 95% CI: −19.5 to 2.0, P = 0.005), PTH (−1.1 pmol/L, 95% CI: −1.7 to 0.2, P = 0.009) and leptin (−1687 pg/mL, 95% CI −4524 to −563, P = 0.01) declined following SG. Change in FGF23 was not significantly associated with change in measures of adiposity, PTH or leptin. Conclusions: FGF23 concentrations decline in the setting of significant weight loss following SG, implying that increased FGF23 concentrations are a downstream consequence of obesity, which may confound its association with cardiometabolic dysfunction. Mediators of the relationship between adiposity and FGF23 require further elucidation.